2018
DOI: 10.1002/jctb.5634
|View full text |Cite
|
Sign up to set email alerts
|

Growing Chlorella vulgaris on mixed wastewaters for biodiesel feedstock production and nutrient removal

Abstract: BACKGROUND Large water footprint and nutrients demand are two of the major issues during microalgae cultivation. In this study, anaerobically digested swine manure was mixed with centrate at different minimal dilution multiples (2×, 3×, 4×, 6× and 8×), which was used as media to cultivate Chlorella vulgaris (UTEX 2714) for reducing the production cost of algae cultivation and balancing the nutrient profiles of culture media. RESULTS Chlorella vulgaris (UTEX 2714) grew well on the mixed wastewaters with a bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Microalgae desirability is related to their biochemical compositions, such as protein, carbohydrate, lipids and pigments, whose synthesis and accumulation would be affected by the cultivation conditions where they are cultivated . Based on the biomass of C. kessleri , changes of biochemical compositions with culture conditions were evaluated and depicted in Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Microalgae desirability is related to their biochemical compositions, such as protein, carbohydrate, lipids and pigments, whose synthesis and accumulation would be affected by the cultivation conditions where they are cultivated . Based on the biomass of C. kessleri , changes of biochemical compositions with culture conditions were evaluated and depicted in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Microalgae desirability is related to their biochemical compositions, such as protein, carbohydrate, lipids and pigments, whose synthesis and accumulation would be affected by the cultivation conditions where they are cultivated. 44 Based on the biomass of C. kessleri, changes of biochemical compositions with culture conditions were evaluated and depicted in Fig. 5, which showed that contents of protein, carbohydrate, lipids and pigments in the algal cells were 50.6%, 17.2%, 24.7% and 2.47%, respectively, when this alga was cultivated in the photoautotrophic cultures.…”
Section: Biochemical Compositions Of Algal Biomassmentioning
confidence: 99%
“…Similar results were reported by Zheng et al . and Deng et al ., who found that the mixture of different wastewaters had a better nutrient profile for algae growth than the individuals.…”
Section: Resultssupporting
confidence: 91%
“…The fatty acids profiles were different with the change of dilution multiple of ADE. The predicted properties of biodiesel fit for the biodiesel standards of ASTM D6751-08 and EN 14214 [72] . Chung et al [68] cultivated Spirulina sp.…”
Section: Nutrient Removal and Biomass Production By Microalgae Cultivated In Adementioning
confidence: 84%
“…Additionally, some studies also investigated the chemical compositions in the microalgae from the ADE media, such as pigments, carbohydrate, protein and lipids, especially the fatty acids profiles which could be a potential way to determine some important properties of biodiesel [57,72] . Deng et al [72] investigated the potential biodiesel feedstock production and nutrient removal of Chlorella vulgaris (UTEX 2714) cultivation in the anaerobically digested swine manure. The fatty acids profiles were different with the change of dilution multiple of ADE.…”
Section: Nutrient Removal and Biomass Production By Microalgae Cultivated In Adementioning
confidence: 99%